Preparation of porous inorganic hollow fibre membranes by a combined phase-inversion and sintering method for waste water treatment - Liu, Shaomin; Meng, X.; Liu, L.; Tan, X. (Nova Science publishers, INC, USA, 2015)
Due to their high mechanical strength and material stability, porous inorganic membranes have been widely used in water treatment to remove various contaminants. In light of their pore size distribution, they can be applied for molecular sieving (0.1 - 0.5 nm), reverse osmosis (0.1 - 1 nm), nanofiltration (1 - 100 nm), ultrafiltration (0.01 - 0.1μm), microfiltration (0.1 - 5μm) and filtration (1 - 200 μm). Some of these membranes with pore sizes between 0.1 to 2 μm can be prepared in one sintering step from these commercially available ceramic powders. However, other membranes with smaller pore sizes, less than 0.1 microns, have to be prepared in an asymmetric structure via multi - steps, i.e., a thin layer supported on a porous substrate. The geometry of inorganic membranes can be in tubular, flat - sheet, multi - channel, or hollow fibre. For the organic membranes, one of the most popular configurations is a polymeric hollow fibre, which can be prepared by a non - solvent - induced phase inversion method. The same phase inversion method can be revised to prepare the inorganic hollow fibre membranes. Since the first patent to introduce this method to prepare inorganic hollow fibres in the early 1980s, various hollow fibre membranes in different inorganic materials have been progressively developed. This book chapter is focusing on this special area of using phase inversion method to prepare the porous inorganic hollow fibre membranes covering the state of the art, challenges and future works.